2009
DOI: 10.1590/s1678-77572009000500007
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of a nanofill composite: effect of different immersion media

Abstract: Objective:The aim of this in vitro study was to evaluate the color stability of a nanofill composite resin (Filtek Z350) in different immersion media.Materials and methods:Twelve resin-based composite specimens were prepared using a silicon cylindrical mold measuring ≅1mm of thickness and ≅ 10mm of diameter. Specimens were light-cured for 40 s from both sides using a LED Radii at 1400 mW/cm2 and were randomized into 4 groups (n= 3) according to immersion media: coffee, yerba mate, grape juice or water (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
185
0
37

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(228 citation statements)
references
References 17 publications
6
185
0
37
Order By: Relevance
“…Here, we used the CIE L * a * b * system to evaluate ΔE * . Although some recent studies have demonstrated that another measurement system, i.e., CIEDE2000, may provide a better fit than the former in the evaluation of color difference thresholds, 10,18,19,20 many other studies use the CIE L*a*b* color system to analyze color outcomes in dentistry 3,5,21,22,23 because this system features predictability and clinical importance. ΔE * did not increase after 12 months of storage in specimens prepared with the modeling liquids.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used the CIE L * a * b * system to evaluate ΔE * . Although some recent studies have demonstrated that another measurement system, i.e., CIEDE2000, may provide a better fit than the former in the evaluation of color difference thresholds, 10,18,19,20 many other studies use the CIE L*a*b* color system to analyze color outcomes in dentistry 3,5,21,22,23 because this system features predictability and clinical importance. ΔE * did not increase after 12 months of storage in specimens prepared with the modeling liquids.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained color stability of dental restorative materials remains a challenging factor as it differentiates between restorations' success and failure [1,2]. In this context, materials' properties and fabrication techniques play an important role determining the behavior of the material, which ensure restorations' success.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [2][3][4][5][6][7][8] in the literature have shown that foods and beverages present in patients' diet, especially those containing alcohol, 33 sugar 3,26 and acid 12,16 in their composition, can promote change in the color of esthetic restorative materials. The KAPO  juice used in this study, irrespective of the flavor tested, has citric acid and sugar in its composition, but possibly in insufficient amount to promote color change.…”
Section: Discussionmentioning
confidence: 99%
“…However, when this material is present in the oral environment, it becomes vulnerable to the infl uence of some factors that may result in staining [2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation